Adhesion and Signalling Molecules Controlling the Extravasation of Leukocytes across the Endothelium - Engelhardt, Britta (S. Karger GmbH, 2008)
SUMMARY: To ensure proper immunosurveillance, lymphocytes continuously recirculate throughout our body searching for their specific antigens. For their transportation to the distant destinations they use the blood vessels, which they leave once they have reached their target tissue. Lymphocytes exit the different organs via the lymphatic vascular system, which due to its connection to the venous blood stream allows the immune cells to re-enter the blood stream. Lymphocyte recirculation is not random, rather a sophisticated navigation system allows immune cells to ‘read’ organ-specific traffic signals posted at the blood vessel wall within each organ. These traffic signals ensure that the appropriate immune cell reaches its proper location at the right time. Here, I will describe the steps involved in immune cell trafficking in our body and briefly introduce the molecular nature of the immune cell navigation system and the vascular traffic signals required for this process.